Data Management for Evaluating Complications of Health Care - Streed, Stephen A. (1988)
This paper describes the design and operating characteristics of a microcomputer-based data management system for assessing complications associated with the delivery of health care. The system was developed in response to the need to promote “risk management” as an essential component of the Quality Assurance effort within the health care delivery environment. The system herein described allows the epidemiological evaluation of complications of health care in a tertiary care referral center.